Isolation and Expression Analysis of Ethylene Receptor Gene from Oncidium Gower Ramsey Flower - Mohamed Bahari, Umikalsum (2009)
The process of flower senescence is influenced by the plant hormone, ethylene. In Arabidopsis, ethylene perception is controlled by a family of five genes, including ETHYLENE RESPONSE 1 (ETR1), ETHYLENE RESPONSE SENSOR 1 (ERS1), ETHYLENE RESPONSE 2 (ETR2), ETHYLENE RESPONSE SENSOR 2 (ERS2) AND ETHYLENE-INSENSITIVE 4 (EIN4). They fall into two subfamilies based on their sequence similarities. In flower, it has been reported that similar set of genes are also involved. This study was carried out to isolate the gene that is involved in ethylene signaling from Oncidium Gower Ramsey flower. Total RNA was extracted from self-pollinated Oncidium Gower Ramsey flowers followed with reverse transcriptase-polymerase chain reaction (RT-PCR) using two degenerate primer pairs (F1/R1 and F2/R2). These primers were designed based on the conserved regions of ethylene receptor genes of various plant species. Fragments of the expected size were yielded and sequenced. DNA sequences analysis showed a very high homology to the full length ethylene receptor gene, ETHYLENE RECEPTOR 2 (ER2) (Genebank AF276234) of Oncidium Gower Ramsey. From here, specific primers (F3/R3) were designed for 5’ and 3’ ends of the open reading frame (ORF) region of the ER2 gene in order to clone a similar full length gene. The purified and sequenced PCR fragment had 98% DNA sequence similarity to the ER2 gene. However, the newly amplified fragment was only 1595bp, encoded for 422 amino acids as compared to the 2389bp (631 amino acids) of the full length ER2. Sequence alignment of the two genes indicated two truncated regions between nucleotide number 1015 to 1643 (628bp) and 2013 to 2027 (14bp). These results demonstrated that we have cloned an ethylene gene named ER25, which encodes for a protein that has a missing region in the histidine kinase domain as compared to the sequence of ER protein for a similar orchid hybrid. In addition, expression of the isolated gene was detected by real-time RT-PCR at a very low level in the tested flower tissues, as well as in roots. Our results suggest that ER25 may be involved in the development of different plant tissues